Tuning of mechanical properties of Ti1?xAlxN coatings through Ta alloying; Surface and Coatings Technology; Vol. 382 - Shugurov A. R. Artur Rubinovich; Kuzminov E. D. Evgeny Dmitrievich; Kasterov A. M. Artur Maksimovich; Panin A. V. Alexey Viktorovich; Dmitriev A. I. Andrey Ivanovich (2020, 2020)
Title screen